2003
DOI: 10.1177/1052562903252652
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Case Method on Tolerance for Ambiguity

Abstract: This research examined the effect of the case method of teaching the strategic management course on students' tolerance for ambiguity. Ambiguity tolerance, locus of control, and several demographic variables were assessed at pre- and postcourse intervals to determine if ambiguity tolerance increased with the use of narrative cases. When compared to the control group, the results suggest that case teaching can improve ambiguity tolerance of student participants. Performance in the course was also associated pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 19 publications
0
52
0
4
Order By: Relevance
“…Even though case studies are useful to help students understand multiple issues in complex situations and develop an appreciation of real life management issues in a dialectic of discussion (Liang & Wang, 2004), and develop necessary skills for making and implementing decisions in the real world (Banning, 2003) Reflecting the emphasis on explorative and experiential nature of innovation, instructors tend to not to measure student performance through written examinations which are found to be a poor predictors of long term learning of course content or any subsequent performance, such as success at work (Gibbs & Simpson, 2002). They rely more on creative group activities and reflexive individual tasks.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Even though case studies are useful to help students understand multiple issues in complex situations and develop an appreciation of real life management issues in a dialectic of discussion (Liang & Wang, 2004), and develop necessary skills for making and implementing decisions in the real world (Banning, 2003) Reflecting the emphasis on explorative and experiential nature of innovation, instructors tend to not to measure student performance through written examinations which are found to be a poor predictors of long term learning of course content or any subsequent performance, such as success at work (Gibbs & Simpson, 2002). They rely more on creative group activities and reflexive individual tasks.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Case discussion provides students with a vicarious workplace experience. While the effectiveness of CM has been under researched, one study found that it increases students' tolerance for ambiguity (Banning, 2003). In a world characterized by rapid change and a need for flexibility, this was a powerful outcome.…”
Section: Effectiveness Of CM In Classroom Discussionmentioning
confidence: 99%
“…The case study method is widely used in business schools to explore "the 'wicked' problems that potential managers will face in an uncertain world" 6 and encourage the "development of critical thinking and sense making abilities." 7 Over time, the case study method has become a popular teaching tool because its been shown to help the student connect theory with a practical application that increases the relevance of the potential solution 8 . Case-based instructional methods have long been used in engineering education, almost exclusively in the context of ethics where "there is widespread agreement that the best way to teach professional ethics is by using cases."…”
Section: Case Study Methods Instructionmentioning
confidence: 99%